Safety and Feasibility of Intravenous Paracetamol for Patent Ductus Arteriosus in Indomethacin-/Ibuprofen-Resistant or -Contraindicated Preterm Infants: A Case Series - Ayumi Oshima; Shun Matsumura; Ayaka Iwatani; Machiko Morita; Sumie Fujinuma; Yukiko Motojima; Kosuke Tanaka; Satoshi Masutani; Kazuhiko Kabe; Keiko Ueda; Fumihiko Namba (Thieme Medical Publishers, Inc., 2020)
Background Although indomethacin and ibuprofen are the standard treatments for hemodynamically significant patent ductus arteriosus (hsPDA), they are associated with renal impairment and gastrointestinal complications. Paracetamol for hsPDA closure does not provoke a peripheral vasoconstrictive effect and seems to have effects similar to those of indomethacin and ibuprofen. We have previously reported the safety of low-dose (7.5 mg/kg) intravenous paracetamol for preterm infants with hsPDA, who were indomethacin-resistant or -contraindicated but did not affect the need for surgical PDA ligation. However, reports considering the use of higher-dose (15 mg/kg) paracetamol for hsPDA have not been published in Japan. Cases In 16 premature infants in whom indomethacin or ibuprofen was contraindicated or ineffective, 15 mg/kg of paracetamol was intravenously administered every 6 hours for 3 days after obtaining parental consent. hsPDA closure or narrowing was observed in 14 infants (88%), with the need for surgical closure totally avoided in nine cases (56%). High plasma paracetamol levels were observed in three cases. No paracetamol-related side effects or adverse events were reported. Conclusion The intravenous administration of higher dose paracetamol was safe and feasible in premature infants with hsPDA. Future clinical trials to explore the optimized dose and timing of administration are needed.